Pengaruh Strategi Pemecahan Masalah Wankat-Oreovocz dan Pembelajaran Teknik Probing terhadap Kemampuan Literasi Matematis Siswa SMP - Linuhung, Nego (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
Low of mathematical literacy become this research base. Alternative solution in overcoming the problem is needed absolutely, so this research aim to analyze the essence of learning the strategy of Wankat-Oreovocz problem solving and the Probing Technique learning as alternative the problem solution. The research design which is used is a non-equivalent control group design by using technique of Purposive Sampling. The Research Subject is all eight grade students of Sukahaji Junior High School with the research sample is eight grade students. The research instrument used in the form is mathematical literacy test of level 5, teaching materials and questionnaire. Result of the research indicates that: There is not the difference of mathematical literacy of level 5 at student who is getting strategy of Wankat-Oreovocz problem solving (WO) and the Probing Technique learning (TP)